The Effect Of Public Relations On Increasing Service Users At International Airports Kualanamu District Deli Serdang - Ziko, Randi Yafran; Handayani, Benni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Kualanamu International Airport Kab. Deli Serdang as one of the entry gates for domestic or international tourists to North Sumatra, which was previously at Polonia Medan Airport, which is managed by Angkasa Pura II, greatly influences the comfort of service users through the information provided to passengers so that passengers feel comfortable while waiting for departure. aircraft. By looking at the relatively large interest of users of air transportation services, they require services at Angkasa Pura II Airport which involve effective and efficient public relations to bring potential service users back. In addition, this public relations approach greatly stimulates the interest of service users by providing information services, flight schedules, changes in departure times, and others until service users are satisfied and bring in other service users at Kualanamu International Airport Kab. Deli Serdang. Keywords: Public Relations, a